Nontargeted Metabolomic Analysis of Four Different Parts of Platycodon grandiflorum Grown in Northeast China - Wang, Cuizhu (Molecules, 2017)
Platycodonis radix is extensively used for treating cough, excessive phlegm, sore throat, bronchitis and asthma in the clinic. Meanwhile, the stems, leaves and seeds of Platycodon grandiflorum (PG) have some pharmaceutical activities such as anti-inflammation and anti-oxidation effects, etc. These effects must be caused by the different metabolites in various parts of herb. In order to profile the different parts of PG, the ultra-high performance liquid chromatography combined with quadrupole time-of- flight mass spectrometry (UPLC-QTOF-MS(E)) coupled with UNIFI platform and multivariate statistical analyses was used in this study. Consequently, for the constituent screening, 73, 42, 35, 44 compounds were characterized from the root, stem, leaf and seed, respectively. The stem, leaf and seed contain more flavonoids but few saponins that can be easily discriminated in the root. For the metabolomic analysis, 15, 5, 7, 11 robust biomarkers enabling the differentiation among root, stem, leaf and seed, were discovered. These biomarkers can be used for rapid identification of four different parts of PG grown in northeast China.